Population diversity of insect-pest and beneficial insects at paddy field in Sawah Sempadan, Selangor / Nor Halina Mohd Nadzri - Mohd Nadzri, Nor Halina (Faculty of Plantation and Agrotechnology, 2017)
Modern agriculture mostly relies on chemicals in order to control insect-pest resulting in the deterioration and imbalance of the ecosystem in the paddy field. Additionally, climate factors also have fraction towards ecosystem, hence, it affected on the diversity and distribution of insects. Insect diversity studies were conducted for five weeks of sampling period at paddy (Oryza sativa L.) field, Sawah Sempadan, Selangor to assess the population diversity of insect pest and beneficial insect, thus, can evaluate the relationship between insect pest and beneficial insect with climate factors. Insects were collected randomly by using yellow sticky traps and sweeping net. Insect diversity in Sawah Sempadan, Selangor paddy field has been changing over the time which the increasing value of diversity is proportional to week sampling. The results were indicated as Homoptera (4.37) as it had the highest diversity of insects, but, Hemiptera (32.60%) as the dominant order and the negative correlation between insect populations toward humidity climate. Araneidae is the only predator of insects pest that has positive correlation to temperature climate. Araneidae (beneficial organism) such as Riptortus linearis and Nezara viridula (insect-pest) were recorded as negative correlation. Hence, it showed that the beneficial insects are highly potential to conserve ecology and suppress insect-pest in paddy field.